The Effect of Shuttle-Run and Zig-Zag Exercises on Ball Dribbling Ability in Students of Public Junior High School 27 Palembang - Apraja, Putu Surya; Manullang, Jujur Gunawan; Putri, Siti Ayu Risma (Journal of Social Work and Science Education, 2023)
The purpose of this study was to determine the effect of the Shuttle-Run and Zig-Zag exercises on ball dribbling skills in SMPN 27 Palembang. This research was conducted on students of SMP Negeri 27 Palembang. The sample of this research was students of class VII.2 and VII.3 with a total of 58 people. The sampling technique uses total sampling. Data collection was carried out by carrying out a dribbling test in a soccer game. The research method uses the experimental method, while the analytical method used is the t test with the SPSS for Windows version 23.00 program. The conclusions of this study are: (1) there is an effect of shuttle-run training on ball dribbling skills in students of SMP Negeri 27 Palembang; (2) there is an effect of zig-zag training on the ball dribbling ability of students at SMP Negeri 27 Palembang.